Manager’s role in career development - Dinç, Burçin (My University, 2002)
The objective of this study is to investigate the manager's role in career development. In order to analyze this topic, the basic subjects have been explained. It is important to understand the career concept and its development to understand the manager's role in this process. In modern organizations, serious attention has been directed to the way careers development. Individual, organizational and societal forces shape this development. An individual needs to understand career progress in order to manage his/ her own career more effectively. This understanding of career progress can be a great aid to the; individual himself/ herself, manager and the organization. The important issue in career development is the ability to provide a bridge between the organization and the individual. Therefore, the manager is the one that could help to create a match between the organization' s needs and the employee's needs. The manager is the one who could direct the career decision for both of them. Managers in the organizations need the results of this development. While the manager's prime responsibility is to manage a group of subordinates, one of the subordinate's prime concerns is to manage his/ her own career. Therefore, the manager who can understand career interest and career dynamics will be more effective in managing and developing his/ her employees. This study is divided into four basic parts. A general discussion of the general concepts career, career development and the manager has been examined in the first part. In the second part the theoretical and conceptual framework for understanding the career development process has been analyzed. The third part is about the manager's role in career development. A literature survey on the topics of career, career development and the manager's role in this process is used for the theory parts. After a through exploratory research, the effectiveness of the manager's role in their employee's career development has been revealed with a questionnaire.

Bu çalışmanın amacı, kariyer geliştirme sürecinde yöneticilerin rolünün incelenmesidir. Konunun derinliğine incelenebilmesi için öncelikle temel kavramlar açıklanmıştır. Kariyer ve kariyer geliştirme süreçleri incelenerek, bu süreç içerisinde yöneticinin rolünün önemi vurgulanmıştır. Modern organizasyonlarda, kariyer geliştirme çalışmaları üzerine odaklanılmıştır. Bireysel ve kurumsal etkiler, kariyer gelişim sürecine yönelik çalışmalara yön vermektedir. Birey, kendi kariyerini etkin bir biçiminde yönetebilmek için, kariyer gelişim sürecini anlamalıdır. Bunun sonucunda bireyin kendisiyle beraber, yönetici ve organizasyon da faydalanacaktır. Kariyer gelişim sürecinde, birey ve organizasyon arasında bir köprü sağlayabilmek çok önemlidir. Yönetici, birey ve organizasyonun ihtiyaçları arasındaki bağlantıyı kurabilecek kişidir. Yönetici, aynı zamanda her iki taraf için de gerekli olan kariyer karalarına yön verebilir. Bunun yanı sıra, yöneticiler bu gelişim sürecinin sonuçlarını elde etmek isterler. Yöneticinin öncelikli sorumluluklarından biri çalışanlarını yönetmek olduğu gibi, çalışanların öncelikli sorumluluklarında biri de kendi kariyerlerini yönetmektir. Bu sebeple, kariyer sürecinin farkında olan yönetici, çalışanlarının gelişiminde ve yönetiminde çok daha etkili olacaktır. Çalışma dört temel bölümden oluşmaktadır. Kariyer, kariyer geliştirme ve yönetici kavramları hakkındaki kısımda incelenmiştir. İkinci kısım, kariyer geliştirme sürecine dair teorik ve fikirsel bir çalışmayı içermektedir. Üçüncü bölüm ise kariyer geliştirme sürecinde yöneticilerin rolü hakkındadır. Kariyer, kariyer geliştirme ve yöneticilerin bu süreç içerisindeki rolü ile ilgili teorik bölümlerde kaynak araştırması yapılmıştır. Açıklayıcı bir araştırmadan sonra, yöneticilerin çalışanlarının kariyer gelişimindeki rolünün etkinliği anket uygulaması ile incelenmiştir.
Keywords: İnsan Kaynakları Yönetimi